Cognitive Impairment Among Elderly Individuals in Shanghai Suburb, China: Association of C-Reactive Protein and its Interactions With Other Relevant Factors. (December 2014) - Chen, Jin-Mei; Cui, Guo-Hong; Jiang, Guo-Xin; Xu, Rui-Fang; Tang, Hui-Dong; Wang, Gang; Chen, Sheng-Di; Cheng, Qi
Objectives: To investigate the association between serum C-reactive protein (CRP) concentration and cognitive impairment as well as interactions between CRP and other relevant factors. Methods: Patients with cognitive impairment and 1 to 2 age- and sex-matched controls nested from a population-based study among residents aged 60 years and older in Shanghai suburb. The associations of serum CRP concentration and other relevant factors were examined with logistic regression analysis. Results: The mean CRP in patients with cognitive impairment was higher than that in controls ( P < .001). The highest quartile of CRP (>4.77 mg/L), abdomen obesity, hypertriglyceridemia, and hyperglycemia was associated with cognitive impairment. Significant interactions were found between increased CRP and hypertriglyceridemia as well as between increased CRP and hyperglycemia on cognitive impairment; and the attributable proportion due to interaction was 82% ( P < .0001) and 37% ( P = .007), respectively. Conclusions: Increased CRP was associated with cognitive impairment, and additive effects of increased CRP with hypertriglyceridemia and hyperglycemia on cognitive impairment were observed among elderly individuals.